Immunohistochemical Expression of CDX2 in Gastroesophageal Junction Biopsies: An Emerging Marker for Early Intestinal Differentiation of Barrett’s Metaplasia - Twisha Adhikari; Vidya Monappa (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Histological diagnosis of Barrett’s oesophagus (BE) in mucosal biopsies is challenging and affected by multiple factors. Goblet Cells (GCs) are not distributed uniformly in BE and is dependent on sampling probabilities. Furthermore, GC Mimickers (GCM) are potential pitfalls in the diagnosis of Intestinal Metaplasia (IM). Alcian Blue (AB) stain has been extensively used in detection of GC’s although it has the limitation of low specificity with positive staining for GCM. Recently, CDX2 Immunohistochemistry (IHC) is reported to be highly sensitive and specific marker which has shown to identify early intestinal phenotype even in absence of diagnostic GCs and especially pertaining to conditions where characteristic morphological changes are not apparent. Aim: To study the histomorphology of non neoplastic and neoplastic lesions of the Gastroesophageal Junction (GEJ) in reflux patients and evaluate the diagnostic role of CDX2 IHC versus AB stain in detecting IM. Materials and Methods: This retrospective study was conducted in Department of Pathology at Kasturba Medical College, Manipal, Karnataka, India, on 55 patients with clinical features of reflux and adequate records of GEJ biopsies, diagnosed over 6 years from January 2012 to August 2018. Clinical presentation, endoscopic findings and histomorphology (18 parameters) were recorded. AB stain and CDX2 (IHC) were performed and evaluated in all cases. A detailed histological evaluation was done for all cases and subsequently, sensitivity, specificity, positive predictive value and negative predictive value of CDX2 IHC to identify early intestinal differentiation was calculated. Results: Of 55 cases, 28 were BE, 19-Reflux oesophagitis (RE) and 8-adenocarcinoma. Heart burn and chest pain were the most common clinical presentations of BE. Endoscopy of BE predominantly showed hiatus hernia with tongue like projections of the gastric mucosa. Histologically, intraepithelial eosinophils and spongiosis were more common features in RE. Barrett’s oesophagus showed columnar epithelium with multilayering, presence of IM with GC (1-20/crypt) along with sub-squamous buried epithelium and splitting of muscularis mucosa. By IHC, as compared to AB; CDX2 IHC was more sensitive (100% vs 78.2%) and specific (96.5% vs 82.6%) for detecting an intestinal phenotype. The five cases (22%) of BE contained only GCM in the biopsy, were CDX2 negative but showed a false positivity for AB. In BE, CDX2 additionally highlighted positivity in non GC columnar cells which were AB negative. The CDX2 showed diffuse positivity in dysplasia with focal strong to absent expression in adenocarcinoma. Conclusion: The CDX2 efficiently differentiated between GC and pseudo GC. Its presence in the absence of AB in non GC columnar cells suggests that it effectively detects intestinal phenotypic features even before morphological features are evident.